Long-term outcomes of infantile spasms in children treated with ketogenic diet therapy in combination with anti-seizure medications in a resource-limited region - Liao, Jianxiang; Hu, Zhanqi; Lin, Sufang; Lu, Xinguo; Wen, Jialun; Duan, Jing; Zou, Dongfang; Zou, Huafang; Yu, Mei; Liu, Liqin; Qiao, Xiaoying; Ye, Yuanzhen (Frontiers in Epidemiology, 2023)
Objective Despite numerous guidelines, the overall outcome of infantile spasms is poor, with only a small number of patients being able to attend school. The purpose of this study was to investigate long-term outcomes. Patients had poor access to the recommended first-line anti-seizure medications (ASMs), such as hormones (corticotropin or prednisolone/prednisone) and vigabatrin, and their alternative treatment was other ASMs and a ketogenic diet. Methods Patients suffering from infantile spasms who had at least 2 years of medical records in the electronic medical record system between January 2014 and August 2022 were included in this study. Patient information was retrospectively reviewed. All patients had received ketogenic diet therapy (mainly classical ketogenic diet therapy). The ketogenic diet therapy was combined with ASMs not used as first-line therapies. The primary endpoint outcome measure was the number of patients with seizure freedom. The secondary measures included the duration of ketogenic diet therapy, choice of ASMs, and patient development at the last visit. Results A total of 177 patients with infantile spasms were included, and 152 (86%) of them had seizure freedom. The median duration from the first to the last hospital visit was 53.27 months, and the number of visits was 47.00. The median age at the initial hospital visit was 8.00 months, and the median age at initiation of the ketogenic diet was 17.73 months. At the last visit, the proportions of patients with neurodevelopmental delay, developmental epileptic encephalopathy, drug-resistant epilepsy, and generalized seizures increased significantly. The frequently used ASMs were topiramate, valproic acid, levetiracetam, nitrazepam, and vitamin B6 injection, while the recommended first-line drugs corticotropin and vigabatrin were rarely selected. The study duration of 9.5 years was divided into three periods but the prescription of ASMs did not change significantly between these periods. Conclusions Although the seizure freedom rate was high with ketogenic diet therapy combined with non-standard ASMs, the patients had a significant neurodevelopmental delay at the last visit, which was, however, similar to that of standard treatment. To improve the outcomes of infantile spasms, multicenter clinical trials of the ketogenic diet as a first-line treatment in combination with non-standard ASMs are needed.